Species diversity and phylogeny of the deep-sea genus Pseudomma (Crustacea: Mysida) - Meland, Kenneth (Zootaxa, 2004)
The mysidacean genus Pseudomma G.O. Sars, 1870 occurs throughout the world s oceans, containing 38 highly endemic and primarily deep sea species. The taxonomic history of the genus and taxonomic status of species currently included in Pseudomma is reviewed. Pseudomma kruppi W.M. Tattersall, 1909 is for the first time recorded from the Pacific Ocean. A comparative study of morphology suggests morphological stasis within the genus Pseudomma, possibly a result of stabilizing selection in a homogeneous deep-sea environment. 71 morphological characters are used to reconstruct Pseudomma phylogeny. The general frequency coding method (GFC) was applied in re-coding 14 polymorphic characters. Fifty-seven conventional characters were treated in separate analyses as either ordered or unordered to investigate how assumptions on character transformation influenced phylogeny. Maximum parsimony searches with both assumptions produced incongruent trees with conflicting branching patterns particularly in deeper nodes. A meaningful interpretation of origin and radiation in early lineages proved to be difficult. Recognition of consistent and more robust branching patterns in several recent lineages suggest monophyletic species groups that are confined within three major geographic areas, North Atlantic, northern Pacific and Antarctic. Branching order could be attributed to speciation events that were in accordance with recent geological history, such as the closing of the Panama Isthmus and establishment of the Norwegian Sea.